1994
DOI: 10.1084/jem.179.4.1379
|View full text |Cite
|
Sign up to set email alerts
|

Production of interleukin 10 by islet cells accelerates immune-mediated destruction of beta cells in nonobese diabetic mice.

Abstract: Sllmm~AFyThe T helper type 2 (Th2) cell product interleukin 10 (IL-10) inhibits the proliferation and function of Thl lymphocytes and macrophages (Mr The nonobese diabetic mouse strain (NOD/Shi) develops a Me and T cell-dependent autoimmune diabetes that closely resembles human insulindependent diabetes mellitus (IDDM). The objective of the present study was to explore the consequences of localized production of IL-10 on diabetes development in NOD/Shi mice. Surprisingly, local production of IL-10 accelerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(135 citation statements)
references
References 35 publications
5
127
2
Order By: Relevance
“…There was a significant increase in frequency of CD8 ϩ T cells and B cells in IL-10.tsF-treated mice. This supports previous work, which has shown that IL-10 can promote the growth of activated CD8 ϩ cells (38,39) and that increased pancreatic infiltration of CD4 ϩ , CD8 ϩ T and B cells were observed in an IL-10 transgenic model in NOD mice (40,41). In contrast to both the transgenic NOD study and the results we present here, transgenic mice constitutively producing human IL-10 (400 -700 pg/ml in serum) were protected from the induction of EAE and failed to show histological evidence of CNS infiltration (42).…”
Section: Discussionsupporting
confidence: 79%
“…There was a significant increase in frequency of CD8 ϩ T cells and B cells in IL-10.tsF-treated mice. This supports previous work, which has shown that IL-10 can promote the growth of activated CD8 ϩ cells (38,39) and that increased pancreatic infiltration of CD4 ϩ , CD8 ϩ T and B cells were observed in an IL-10 transgenic model in NOD mice (40,41). In contrast to both the transgenic NOD study and the results we present here, transgenic mice constitutively producing human IL-10 (400 -700 pg/ml in serum) were protected from the induction of EAE and failed to show histological evidence of CNS infiltration (42).…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the presence of the neomycin reporter gene in genomic DNA from recipient islets suggested that the transferred cells migrated to the pancreas and possibly proliferated in that area. Notably, this result stands in contrast to the results published by the same group, and another group, on transgenic expression of IL-10 in NOD mice, 31,32 illustrating the care needed in interpreting the implications of various models of potential immunotherapy.…”
Section: Used a Murine Retroviral Vector Containingcontrasting
confidence: 89%
“…21,37,38 However, these studies utilized cellular IL-10 which possesses immunostimulatory activities, including enhancing MHC class II expression and inducing cytotoxic T cell differentiation, that are not properties of vIL-10. In addition, recent studies have shown that both vIL-10-transduced islets and hepatic allografts produce biologically relevant amounts of vIL-10 that inhibit alloantigenic lymphocyte proliferation in vitro.…”
Section: Figure 4 Prolonged Survival Of Vil-10 Transduced Allografts mentioning
confidence: 99%
“…5,10,12 However, vIL-10 does not posses the T cell costimulatory activities of cellular IL-10. [20][21][22] Thus, the introduction of vIL-10 into allografts by direct gene transfer should reduce immunogenicity, impair effective antigen presentation, and suppress macrophage and T cell effector function, thereby inhibiting graft rejection.…”
Section: Introductionmentioning
confidence: 99%